Fractional CO2 Laser Treatment of Mild Periorbital Wrinkles in Iraqi Patients - Ayyash, Mazin H.; Mahmood, Ali S. (Iraqi Journal of Laser, 2020)
Background and Objective: Public demand for procedures to rejuvenate photodamaged facial skin have stimulated the use of fractional CO2 laser as a precise and predictable treatment modality. The purpose of this study was to assess the effect of fractional CO2 laser system for reducing periorbital rhytids.Materials and Methods: twenty seven subjects with mild periocular wrinkles, and photoaged skin of the face were prospectively treated two to three times (according to clinical response) in the periorbital area with a fractional CO2 laser device equipped with a scanning hand piece. Improvements in eyelid wrinkles was evaluated clinically and photographically. Subjects also scored satisfaction and tolerability.Results: seventy % of subjects achieved or maintained 50–60% improvement at 3 months. Nearly 40% of subjects maintained 20–40% improvement at 3 months after treatment. Subject satisfaction was high and the procedure was well tolerated. Mild-to-moderate erythema and edema persisted for up to three to four days.Conclusion: Treatment with a fractional CO2 laser device improves periorbital rhytids, and tightens skin.